Suicide deaths and substance use in the Galician provinces between 2006 and 2020 - Flórez, Gerardo; Espandian, Ashkan; Llorens, Noelia; Seoane-Pillado, Teresa; Saiz, Pilar (Frontiers in Psychiatry, 2023)
Background Suicide is a serious public health problem that affects our entire country, including the Galician provinces. The aim of this research was to study the variation in completed suicide rates, between 2006 and 2020, in the different Galician provinces and their relationship with the consumption of addictive substances. Methods Completed suicide data from the Spanish Office for National Statistics and the Institute of Legal Medicine of Galicia were analyzed with a Joinpoint regression model to determine time trends. The relationship between the variation in completed suicide rates with sociodemographic variables obtained from the Spanish Office for National Statistics and variables related to the consumption of substances obtained from the survey on alcohol and other drugs in Spain (EDADES) of the Government Delegation for the National Plan on Drugs was also analyzed. Results The Joinpoint regression model did not reveal any point of significant change in the period studied for any Galician province. The following variables correlated positively with the variation in completed suicide rates in the Galician provinces: masculinity ratio, average age, daily alcohol consumption and daily illegal substance consumption. Conclusion Applying preventive strategies on the daily consumption of alcohol and illegal substances would help reduce the rates of completed suicide in the Galician provinces.